2007
DOI: 10.1111/j.1540-4560.2007.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhabitants' and Experts' Assessments of Environmental Quality for Urban Sustainability

Abstract: In the context of sustainable urban development, we discuss the assessment of residential environmental quality and the importance of considering inhabitants' perceptions of natural resources in urban areas. Two series of studies, conducted in Guildford (United Kingdom) and in Rome (Italy), addressed the correspondence, or contrast, between inhabitants' and experts' assessment of urban quality concerning two crucial natural resources: air quality and biodiversity. The Guildford study emphasized the accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 39 publications
4
45
0
4
Order By: Relevance
“…Kaplan regards this as an important facet of their expertise: they perceive differently because they are experts. In a study by Bonnes and colleagues (Bonnes, Uzzell, Carrus, & Kelay, 2007) it was also concluded that laymen (residents in the quarters being estimated) and experts in plant ecology rated satisfaction with the quality of urban green spaces in the quarters differently. The authors interpreted the results that usability of the urban green spaces was more important to the residents than the amount of biodiversity in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan regards this as an important facet of their expertise: they perceive differently because they are experts. In a study by Bonnes and colleagues (Bonnes, Uzzell, Carrus, & Kelay, 2007) it was also concluded that laymen (residents in the quarters being estimated) and experts in plant ecology rated satisfaction with the quality of urban green spaces in the quarters differently. The authors interpreted the results that usability of the urban green spaces was more important to the residents than the amount of biodiversity in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the urban form is manipulated as a physical form exclusively, it will no longer be capable of keeping up with social and political changes (Bonnes et al, 2007;Soneryd, 2004). A city's form alters due to changes in, for example, political systems and demographic structures.…”
Section: Dialectical Points Related To the Five Issuesmentioning
confidence: 99%
“…In a study on the stream Rekolanoja in the city of Vantaa, for instance, some residents wanted the surrounding environment to be more natural, while other preferred a managed park (YliPelkonen et al 2006). Also, in a survey in Rome, residents appreciated the abundance of natural areas in their neighborhoods, but increasing biodiversity did not necessarily improve their perceived levels of satisfaction (Bonnes et al 2007). In most cases, however, large natural areas can be preserved only on the basis of ecological arguments, and natural areas that hold unique significance for people's everyday lives are not equally valued.…”
Section: Introduction: Urban Nature As Everyday Landscapementioning
confidence: 99%
“…Quality criteria for a positive nature experience can arise from very different interpretative frames and also be internally contradictory (e.g., Bonnes et al 2007; see also Van Herzele, 2004). In a study on the stream Rekolanoja in the city of Vantaa, for instance, some residents wanted the surrounding environment to be more natural, while other preferred a managed park (YliPelkonen et al 2006).…”
Section: Introduction: Urban Nature As Everyday Landscapementioning
confidence: 99%